THE APPLICATION OF THE PAKISTANI TAHFIZH METHOD IN IMPROVING THE QUALITY OF MEMORIZATION OF STUDENTS AT THE UMMUL QURO' TAHFIZH BOARDING SCHOOL PALOPO CITY - Perkasa, Massangadi Teguh; Mawardi, Mawardi; Mustafa, Mustafa (PT. Jurnal Center Indonesia Publisher, 2025)
This thesis discusses the application of the Tahfizh Pakistani Method in improving the quality of memorization of students at the Ummul Quro' Tahfizh Boarding School in Palopo City. This study aims to determine how the process of implementing the Tahfizh Pakistani method and the results of its application to improve the quality of memorization of students. This study uses the Classroom Action Research (CAR) approach of the Kemmis and McTaggart model which consists of four stages: planning, action, observation, and reflection, which are carried out in two cycles. Data collection techniques use observation, documentation, and oral memorization tests. The results of the study showed that the application of the Tahfizh Pakistani method significantly improved the quality of students' memorization. Teacher activity increased from 77.88 % in cycle I to 90.38% in cycle II, while student activity increased from 73.68% to 93.42%. The results of the student memorization test showed that in cycle I, only 6 out of 11 students (54.5%) completed the process, with an average score of 12.18 (very good category ) , while in cycle II it increased to 9 students (81.8%) with an average score of 13.27 (very good category ) . Thus, the application of this method has been proven effective in improving the quality of students' memorization at the tahfizh boarding school.